Area-Wide Management of Fruit Fly Pests. - Perez-Staples, Diana; Diaz-Fleischer, Francisco; Montoya, Pablo; Vera, Maria Teresa (Milton : Taylor & Francis Group, 2019)
This book supplies the latest research on the biology, management procedures, and control strategies of fruit flies of economic importance. It considers an integrative approach covering topics including behavior, genetics, biological control, integrated pest management, host-plant interactions, trap design, and transgenics of fruit flies.
SECTION VIII: Social, Economic, and Policy Issues of Action Programs -- Chapter 27: Compendium of Fruit Fly Host Plant Information: The USDA Primary Reference in Establishing Fruit Fly Regulated Host Plants -- Chapter 28: Tephritid-Related Databases: TWD, IDIDAS, IDCT, DIR-SIT -- Chapter 29: Stewed Peaches, Fruit Flies, and STEM Professionals in Schools: Inspiring the Next Generation of Fruit Fly Entomologists -- Chapter 30: Phytosanitary Education: An Essential Component of Eradication Actions for the Carambola Fruit Fly, Bactrocera carambolae, in the Marajo Archipelago, Para State, Brazil -- Chapter 31: Phytosanitary Education as a Component of Eradication Actions of the Carambola Fruit Fly (CFF) Bactrocera carambolae in the Raposa Serra Do Sol Native Reserve, State of Roraima, Brazil -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books